PENGARUH PERCEIVED SERVICE QUALITY TERHADAP REPURCHASE DAN CUSTOMER SATISFACTION SEBAGAI VARIABEL INTERVENING PADA MCDONALD’S DI KOTA MALANG - Rizky Kurniawan Murtiyanto (Politeknik Negeri Malang, 2018)
The purpose of this research aims to analyze the effects of Perceived Service Quality towards Repurchase with Customer Satisfaction as an intervening variabel in McDonald’s Malang city. This research was conducted by distributing questionnaires to 100 respondents who were customers of McDonald’s Malang city who made transactions in the last six month. This research use the Perceived service quality (X1) variable Customer satisfaction variable (Y1), Repurchase variable (Z1). The results show: (1) Perceived service quality influence significantly effect customer satisfaction; (2) Perceived service quality affect significantly effect repurchase; (3) customer satisfaction has a significant impact on repurchase